NATIONAL AND CULTURAL SPECIFICITY OF MILITARY TERMS IN ENGLISH AND UZBEK (Ustozlar uchun, 2026)
Military terminology represents one of the most dynamic and culturally significant layers of professional vocabulary in every language. It reflects not only military organization and strategic concepts but also the historical memory, national mentality, ideological orientation, and sociocultural values of a particular society. The present study investigates the national and cultural specificity of military terms in English and Uzbek from comparative, semantic, linguocultural, and pragmatic perspectives. The research focuses on the ways military terminology embodies cultural identity, historical development, and social attitudes toward war, defense, heroism, patriotism, and military organization in both linguistic systems. The study demonstrates that English military terminology has largely developed under the influence of globalization, technological modernization, NATO military standards, and Anglo-American military doctrine. In contrast, Uzbek military terminology reflects the historical heritage of Turkic military traditions, the influence of Persian and Arabic military lexicon, Soviet military discourse, and the process of nationalization after independence.